Treatment Patterns, Clinical Outcomes and Health Care Resource Utilisation in Patients with EGFR-mutated Metastatic Non-Small Cell Lung Cancer: A Real-World Study in South Korea - Cliff Molife; Jae Min Cho; Jennifer Lapthorn; Min Ju Kang; Yulia D'yachkova; Sangmi Kim; Sam Colman; Saerom Kim; Agota Szende; Ji Hyun Park; Hee Kyung Ahn; Min Hee Hong; et al. (Adis, Springer Healthcare, 2022)
Abstract Background Despite the dynamic treatment landscape for EGFR mutant-positive metastatic non-small cell lung cancer (EGFRm+ mNSCLC), most of the earlier studies have focused on US or Western populations. Objective The objective of this study was to explore real-world treatment patterns and outcomes of South Korean patients with EGFRm+ mNSCLC. Methods Retrospective chart review of adult patients with EGFRm+ mNSCLC who received systemic treatment between January-2019 and June-2019. Results A total of 162 patients were included from 21 hospitals, with a median follow-up of 15.6 months. Median age was 65.0 years, 22% had central nervous system metastasis, and 57% and 38% had exon 19 deletion and exon 21 L858R, respectively. Among 144 patients (89%) who received first-line EGFR-tyrosine kinase inhibitor, afatinib was most the common (44%), followed by gefitinib (28%) and erlotinib (13%). First-line chemotherapy was more common when an EGFR-mutation was detected after versus before first-line treatment initiation (31% vs 5%). Discontinuation of first-line treatment was mostly due to disease-progression (81%) and toxicity (7%). Among 58 (78%) patients who received second-line treatment, osimertinib was the most common (40%). Most (60%) patients reported ≥1 Grade ≥3 adverse event during first-line treatment. Following initiation of first-line treatment, physician visits and chest X-rays were the most frequent healthcare utilisation events. Rates of emergency-room visits and hospitalization were 12% and 16%, respectively, with a mean length-of-stay of 10.4 days. At 12 months, overall survival rate was 95%, and numerically worse for patients with exon 21 versus 19 mutations. Conclusions Characteristics and clinical outcomes of Korean patients with EGFRm+ mNSCLC in real-world practice were comparable to those observed in clinical trials. As osimertinib was not reimbursed for first-line treatment before study completion, further investigation is warranted to explore evolving treatment practice.